The vicious circle effect: stress as effect and cause in patients with psoriasis - Foks-Ciekalska, Aleksandra; Jarząb, Jerzy; Bożek, Andrzej; Hadas, Ewa; Ziółkowska-Banasik, Dominika; Gumieniak, Kamila; Ciekalski, Wiktor (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Psoriasis is a common immune-mediated, chronic inflammatory disease, causing adverse effects on patients’ quality of life and disease burden. In psychodermatology, psoriasis is included both in the group of dermatological diseases, in which the psychophysiological background plays a key role, and in dermatoses being a potential source of emotional disturbances or being a trigger for the development of secondary mental disorders. A comprehensive view of the patient with psoriasis, not only from the point of view of skin disease, but also as a result of a wide impact of stress, including low self-esteem and inappropriate social perception may have a key influence on improvement of quality of life of these patients.